Community Participation in Handling Waste in Bandar Lampung City Towards Smart City - Faradiba Putri Rahmadani; Agus Triono (Penerbit Goodwood, 2022)
Purpose: The purpose of writing this article is to find out how government policies in Bandar Lampung City are in handling waste and also community participation in waste handling to realize Smart Environment through Smart City. Research methodology: This article is a normative legal research with a statutory approach that explores relevant national legal instruments which are analyzed using descriptive methods. Results: The results showed that the Bandar Lampung City government's policy was carried out by making Bandar Lampung City Regional Regulation No. 5 of 2015 concerning Waste Management in Bandar Lampung City. The handling of waste is carried out through the relevant agencies, namely the Bandar Lampung City Environmental Service. To be able to implement the policies made by the government, community participation is needed, especially in handling waste. Community participation is considered as a real and effective effort in implementing the policy. Limitations: This study examines how the waste handling policy in the city of Bandar Lampung and how the participation of the people of the city of Bandar Lampung in the process of handling waste towards a smart city. Contribution: With this research, it is hoped that it can provide benefits as input and improvement for the relevant government in terms of handling waste and community participation in the city of Bandar Lampung, and can be a reference for other writers who want to raise similar issues.